Serviço de colaboração para a arquitetura ClinicSpace - Kroth, Marcelo Lopes (2011)
Ubiquitous Computing or Pervasive Computing is a new paradigm that aims to provide information and communication technology accessible anywhere, by anyone, available anytime, where computational resources should be integrated into the physical environment in a transparent manner. One of the areas of research on pervasive computing infrastructure is related to hospital settings, because of the characteristics of mobility, collaboration and interruption. In this context, the ClinicSpace project, under development at GMob / PPGI / UFSM, uses the concepts of Pervasive Computing to help physicians while performing their tasks in an hospital settings. The goal is to allow doctors to customize the execution of their tasks, which are managed by a middleware in a pervasive environment. Medical work is highly collaborative because of specialist nature of treatments: physicians from different specialties need to collaborate across time and space. Another important aspect to note is characteristic of the asynchronous communication between these professionals, for example, when changing shift. This thesis presents a Collaboration Service created to support asynchronous collaboration among professionals through the delegation of tasks that are not yet complete, integrated to architecture of the ClinicSpace project. Currently, most studies that focus the collaborative aspects in hospital settings with a base of a pervasive middleware have focused on synchronous collaboration, with several efforts to create mechanisms to help, especially in diagnostics, physically distributed teams. Unlike these approaches, this thesis focuses on the characteristics of asynchronous collaboration in hospital settings, always with central vision in the doctor and the particular way of executing their medical activity. An analysis of the applications performance was made after the modifications to the architecture of ClinicSpace project and the conclusion was that after the introduction of a caching mechanism for the tasks, changes in the architecture remained a performance in the execution of applications in pervasive environment, similar than what they had before the modifications.